GAMBARAN RESILIENSI IBU DARI ANAK PASIEN COVID-19 DI KOTA SALATIGA (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to find out how the picture of a mother's resilience towards her child who is a Covid-19 patient in the city of Salatiga. This research is a type of qualitative research with purposive sampling. The number of research participants involved in this study were three mothers with an age range of 25-60 years and whose children were diagnosed with Covid-19. The results of the study found that the three participants had a different picture of resilience. The first participant (SM) showed that he managed to fulfill the seven resilience aspects). While in the second participant (SA) only four aspects of resilience were met, namely emotion regulation, self-efficacy, impulse control, and problem-analyzing ability. Then the third party (IP) fulfills six aspects, namely emotion regulation, optimism, empathy, self-efficacy, impulse control, and control. This study also found other supporting aspects of resilience besides those described by Reivich & Shatte (2002), in the form of aspects of social support (family and close people) and religion.